Analyzing Social Media Strategy in Korean Music Industries - Ni Wayan Liana Mega Putri; Dianiangriani Dilia (Universitas Medan Area, 2023)
The Korean Wave (K-wave), also known as Hallyu, is the term used to describe the phenomenon of Korean pop culture, including TV dramas, movies, pop music, fashion, and online games, becoming widely popular and shared among the people of Japan, China, Hong Kong, Taiwan, and other Asian nations. Korean pop music, also known as K-pop, became a major component of the second K-wave after the first K-wave's drama-focused craze. Additionally, K-pop's fanbase has grown outside of Asia to the West thanks to the quick adoption of social media platforms like YouTube and Twitter. The popularity of K-pop throughout the world helps to improve the perception of